Dampak Covid-19 pada Pendidikan di Indonesia: Sekolah, Keterampilan, dan Proses Pembelajaran - Rizqon Halal Syah Aji (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
AbstractThe temporary closure of all educational institutions as an effort to prevent the spread of an outbreak of Covid-19 worldwide has an impact on millions of students, including in Indonesia. Disturbances in the teaching and learning process directly between teacher and students as well as the termination of the assessment of learning have an impact on the psychological of students, causing a decrease in the quality of skills. This burden is the responsibility of all elements of education, in particular the government, in facilitating the continuity of schools for all stakeholders in education to conduct distance education. How should Indonesia plan, prepare for and overcome co-recovery 19, to reduce the loss of education in the future.Keywords: Covid-19, school, Stakeholders, Indonesia AbstrakPenutupan sementara lembaga pendidikan sebagai upaya menahan penyebaran pendemi covid-19 di seluruh dunia berdampak pada jutaan pelajar, tidak kecuali di Indonesia. Gangguan dalam proses belajar langsung antara siswa dan guru dan pembatalan penilaian belajar berdampak pada psikologis anak didik dan menurunnya kualitas keterampilan murid. Beban itu merupakan tanggung jawab semua elemen pendidikan khususnya negara dalam memfasilitasi kelangsungan sekolah bagi semua steakholders pendidikan guna melakukan pembelajaran jarak jauh. Bagaimana mestinya Indonesia merencanakan, mempersiapkan, dan mengatasi pemulihan covid 19, untuk menekan kerugian dunia pendidikan di masa mendatang.Kata Kunci; covid-19, sekolah, steakhorders pendidikan, Indonesia